The opposite of everyone [compact disc, unabridged] - Jackson, Joshilyn (Harper Audio, 2016)
Born in Alabama, Paula Vauss spent the first decade of her life on the road with her free-spirited young mother, Kai, an itinerant storyteller who blended Hindu mythology with southern oral tradition to re-invent their history as they roved. But everything, including Paula's birth name Kali Jai, changed when she told a story of her own-one that landed Kai in prison and Paula in foster care. Separated, each holding secrets of her own, the intense bond they once shared was fractured.